URGENSI KEPASTIAN HUKUM HAK ATAS TANAH BAGI INVESTOR DI KOTA JAYAPURA - Ningrum Ambarsari (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Socialization of UUPA in Jayapura is not maximized in its implementation in the area. It can be seen from the dominance of local customary laws which affect the control and ownership of land. For that to investors who will invest obtain legal certainty it is necessary perception of the status of the lands of the legacy of the Dutch government after Oveerenkomst; local regulations custom after special autonomy and the role of the head of customs (Ondoafi) in the resolution of land disputes. Legal certainty is needed because the number cases related to land in Jayapura and Papua in general very complicated resolved.Keywords: UUPA, Investors, Legal Certainty